PENGEMBANGAN MODUL METODE NUMERIK MAHASISWA MATEMATIKA STKIP MUHAMMADIYAH PAGARALAM. - Novi Susanti; Ria Erviana (Jurnal Math-UMB.EDU, 2019)
This research is a development research which aims to (1) produce matematic module numeric method is valid and practical at STKIP Muhammadiyah Pagaralam. The research method consist of two stage: (1) preleminary, includes analysis and design of teaching materials in the form of module, (2) formative stages of study includes self evaluation, experts review, one to one and small group. The research subject were student of STKIP Muhammadiyah Pagaralam. Data collection was done by walk trought, documents, and observations. All data collect were analyzed descriptively. Based on the result of the data analysis, it was concluded that (1) this research has produced in a product in the form of module numeric methode is valid and practical. Valid drawn from the assessment and advice of validators, which otherwise well-developedÂ  module according to content (corresponding curriculum SBC), construct, and language (in accordance with EYD). Practical drawn from the test result, which module easy to wear, with the track students minds, not to cause a variety of interpretations and can be supplied and used by the students.